Effectiveness of deep breathing and body scan meditation combined with music to improve sleep quality and quality of life in older adults - Nitayapa Nanthakwang (2020)
© 2020 Nanthakwang et al. Background: In older adults, physiological changes affect sleep and may cause impaired daily function and Reduced Quality of Life (QOL). This study aimed to investigate the effectiveness of deep breathing exercises and body scan meditation combined with music to improve sleep quality and QOL. Methods: A randomized controlled trial with allocation concealment method was conducted. Fifty-nine older adults with poor sleep quality were recruited using block randomization to intervention and control groups. The intervention group was instructed to do deep breathing and body scan meditation while listening to music through Bluetooth speakers once a day for thirty minutes before sleeping, a daily practice to last for eight weeks. The Pittsburgh Sleep Quality Index (PSQI) and Pictorial Thai Quality of Life (PTQL) were administered to both groups prior to the intervention and 8-week post-baseline of the intervention. Results: The global PSQI in the intervention group significantly decreased following the intervention, whereas the control group showed no difference. There was a decrease in individual PSQI components as well for the intervention group, namely, sleep efficiency, perceived sleep quality, and daily disturbance. The intervention group did not differ from the control group in sleep efficiency or perceived sleep quality, but there was a significant difference in the daily disturbance. Additionally, the total PTQL in the intervention group significantly increased between the two time periods, whereas there was no difference in the controls. The intervention group scored higher in each domain of PTQL, except for the economic domain. Conclusion: A daily practice of deep breathing and body scan meditation combined with music has a positive effect on improving sleep quality and QOL among older adults. Hence, this intervention should be implemented to improve sleep quality and promote QOL in older adults.